2020
DOI: 10.1634/theoncologist.2020-0514
|View full text |Cite
|
Sign up to set email alerts
|

The Hospitalist Model and Oncology: Oncologist Opinions About Inpatient Cancer Care Delivery

Abstract: Hospitalists, rather than oncologists, are increasingly providing inpatient medical care to hospitalized patients with cancer, yet the opinions of oncologists regarding this model of care delivery are unknown. A survey was conducted assessing these opinions and experiences with inpatient cancer care delivery at a tertiary cancer center. Only 30% of oncologists agreed that caring for hospitalized patients with cancer was an efficient use of their time, and most believed a hospitalist service allowed them to pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
(8 reference statements)
2
10
0
Order By: Relevance
“…The trend of dedicated inpatient physicians caring for hospitalized patients continues to grow, and studies investigating this care model have shown decreased lengths of stay, lower costs, and improved outcomes for certain patient populations. 2,3,[5][6][7][8][9][10] Changes in outcomes with the use of dedicated inpatient board-certified oncologists to supervise house staff teams caring for oncology patients has not been described in the literature to the best of our knowledge. Data from our institution show that ONC Hosp teams resulted in decreased 30-day readmission rates and increased rates of discharge to hospice with no significant difference in LOS or inpatient mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The trend of dedicated inpatient physicians caring for hospitalized patients continues to grow, and studies investigating this care model have shown decreased lengths of stay, lower costs, and improved outcomes for certain patient populations. 2,3,[5][6][7][8][9][10] Changes in outcomes with the use of dedicated inpatient board-certified oncologists to supervise house staff teams caring for oncology patients has not been described in the literature to the best of our knowledge. Data from our institution show that ONC Hosp teams resulted in decreased 30-day readmission rates and increased rates of discharge to hospice with no significant difference in LOS or inpatient mortality.…”
Section: Discussionmentioning
confidence: 99%
“…9 A survey of oncologists at a tertiary care center showed that a minority felt that attending on the inpatient service was an efficient use of their time and most felt that hospitalists could appropriately diagnose and manage toxicities related to cancer and cancer treatment. 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality and efficiency of hospitalist care in both general inpatient medical units [5][6][7][8] and in subspecialty settings [9][10][11][12][13][14][15] has been well-established. Despite growth in dedicated oncology hospitalist programs at major cancer centers, [9][10][11][12]14,15 little has been published on key quality outcomes, including length of stay (LOS), early discharges, and 30-day readmission rates. In this manuscript, through the implementation of a real-time, direct comparison between a oncologist-led, traditional service (TS) and a hospitalist service (HS), we assess the impact of a hospitalist-driven model on LOS, early discharge rate, and 30-day readmission rate on an inpatient oncology service.…”
Section: Introductionmentioning
confidence: 99%
“…The quality and efficiency of hospitalist care in both general inpatient medical units [5][6][7][8] and in subspecialty settings [9][10][11][12][13][14][15] has been well-established. Despite growth in dedicated oncology hospitalist programs at major cancer centers, [9][10][11][12]14,15 little has been published on key quality outcomes, including length of stay (LOS), early discharges, and 30-day readmission rates.…”
Section: Introductionmentioning
confidence: 99%